Integrating Critical Thinking in an English Speaking Coursebook Speak Now 1 : A Bloomâ€™s Taxonomy-Based Evaluation - Setiawan, Wawan; Surista, Ade (Jurnal Paedagogy, 2025)
This study evaluates the integration of critical thinking skills in the Speak Now 1 English coursebook, specifically in the context of the STBA JIA Basic Speaking course. A mixed-method approach was employed, including qualitative content analysis of 32 speaking activities and a quantitative survey analysis involving 41 students. The speaking activities were analyzed using the revised Bloom's Taxonomy to determine the cognitive domains involved and the questionnaire was gauged studentsâ€™ views on the integration of critical thinking through frequencies and percentages. The findings revealed that all six cognitive domains were present in the coursebook with â€œunderstandingâ€ accounting for the largest percentage, followed by â€œapplyingâ€, and â€œcreatingâ€ and the least prevalent domains were â€œevaluatingâ€ and â€œanalyzingâ€. Meanwhile, students displayed positive perceptions of incorporating critical thinking into the coursebook. However, the study found that the cognitive domains of speaking activities were not structured hierarchically according to a hierarchical system of the revised Bloomâ€™s Taxonomy and that higher-order thinking skills (HOTS) were underutilized. The study suggests that teachers could equip the coursebook with additional tasks targeting â€œanalyzingâ€ and â€œevaluatingâ€ domains and it highlights the importance of balancing cognitive domains in speaking coursebooks in order to promote critical thinking skills in speaking classes.